PENERAPAN KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN BAHASA INDONESIA KELAS VII MTS SIROJUL ISLAM OMBUL SABUNGAN TAHUN AJARAN 2023/2024 - Asri Bariqoh; Hasanuddin; Amirul Mukminin (Jurnal Cendekia Pendidikan, 2024)
The curriculum in Indonesia has undergone several changes. Each curriculum is used for approximately 10 years. The curriculum that is still used is the 2013 curriculum until now. Apart from that, the curriculum is also seen as an educational program that is planned and implemented to achieve educational goals. The research approach in this thesis is descriptive qualitative type. Data collection techniques in this research used observation, interviews and documentation. Meanwhile, data analysis used in research uses data collection, data reduction, data presentation, and drawing conclusions. Checking the validity of the data uses technical triangulation and source triangulation. The results of this research are: 1) Independent learning curriculum planning for class VII Indonesian language subjects at MTs Sirojul Islam Ombul Sabungan for the 2023/2024 academic year in Indonesian language learning is carried out independently by analyzing Learning Achievements, formulating learning objectives, developing a Flow of Learning Objectives, preparing Teaching Module, preparation of Learning Evaluation Types. The implementation of the Independent Learning Curriculum is carried out face to face through preliminary activities, core activities include the use of teaching materials, learning media in the form of projectors, application of the Make a Match and Talaqqi methods, and finally the closing activities. Evaluation of the Independent Learning Curriculum uses three assessments, namely a Diagnostic assessment which is carried out before the implementation of learning, a Formative assessment during the implementation of the learning process, and a Summative assessment at the end of a material, the end of a semester and the end of a phase using assessment techniques in the form of tests and non-tests. 2) Results Obtained from the Implementation of the Independent Learning Curriculum in class VII Indonesian language subjects at MTs Sirojul Islam Ombul Sabungan, namely: There is development of student competence through flexible learning, Achievement of Learning Goals through the cultivation of the Pancasila Student Profile which is also starting to develop.